Association of Antibiotics, Airway Microbiome and Inflammation in Infants with Cystic Fibrosis. - Pittman, J.; Wylie, K.; Akers, K.; Storch, G.; Hatch, J.; Quante, J.; Frayman, K.; Clarke, N.; Davis, M.; Stick, S.; Hall, Graham; Montgomery, G.; et al. (2017)
RATIONALE: The underlying defect in the cystic fibrosis (CF) airway leads to defective mucociliary clearance and impaired bacterial killing, resulting in endobronchial infection and inflammation that contributes to progressive lung disease. Little is known about the respiratory microbiota in the early CF airway and its relationship to inflammation. OBJECTIVES: To examine the bacterial microbiota and inflammatory profiles in bronchoalveolar lavage fluid and oropharyngeal secretions in infants with CF. METHODS: Infants with CF from U.S. and Australian centers were enrolled in a prospective, observational study examining the bacterial microbiota and inflammatory profiles of the respiratory tract. Bacterial diversity and density (load) were measured. Lavage samples were analyzed for inflammatory markers (interleukin-8, unbound neutrophil elastase, and absolute neutrophil count) in the epithelial lining fluid. RESULTS: Thirty-two infants (mean age 4.7 months) underwent BAL and oropharyngeal sampling. Shannon diversity strongly correlated between upper and lower airway samples from a given subject, though community compositions differed. Microbial diversity was lower in younger subjects and in those receiving daily anti-staphylococcal antibiotic prophylaxis. In lavage samples, reduced diversity correlated strongly with lower interleukin-8 concentration and absolute neutrophil count. CONCLUSIONS: In infants with CF, reduced bacterial diversity in the upper and lower airways was strongly associated with the use of prophylactic antibiotics and younger age at the time of sampling; less diversity in the lower airway correlated with lower inflammation on bronchoalveolar lavage. Our findings suggest modification of the respiratory microbiome in infants with CF may influence airway inflammation.